Helping ELLs Meet Standards in English Language Arts and Science: An Intervention Focused on Academic Vocabulary. Issue 4 (3rd July 2016) - August, Diane; Artzi, Lauren; Barr, Christopher
Abstract : The Common Core State Standards and the Next Generation Science Standards require students to understand and produce academic language that appears in informational text. Vocabulary is a critical domain of academic language, but English language learners (ELLs) come to the English Language Arts classroom with more limited English vocabulary than their English-proficient peers. This study compared 2 methods of vocabulary instruction: extended vocabulary instruction and embedded vocabulary instruction. Teachers implemented both approaches in the context of interactive shared reading, in which teachers and students read and discussed informational text. A total of 30 teachers in 18 schools and 509 third- and fourth-grade Spanish-speaking ELLs in a large, high-poverty district in the southwestern United States participated. Findings indicate that although extended instruction was the more effective approach, embedded instruction also helped ELLs acquire general academic and domain-specific vocabulary—an important finding, given that embedded instruction requires considerably less instructional time.